Analisis perbandingan pengelolaan keuangan di Desa Pineleng Satu Timur dan Desa Lotta berdasarkan Permendagri Nomor 20 Tahun 2018 - Imbing, Grasela Feini; Tinangon, Jantje J.; Budiarso, Novi Swandari (Riset Akuntansi dan Portofolio Investasi, 2024)
Village Financial Management encompasses planning, implementation, administration, reporting, and village financial accountability, as outlined in Permendagri Number 20 of 2018. Villages are granted adequate authority and financial resources to manage their potential for improving the economy and welfare of residents, as well as for village development activities. The village government plans to implement the project using funds from the Village Budget (APBDes). The objective of this study is to determine whether financial management in Pineleng Satu Timur Village and Lotta Village, Pineleng District, Minahasa Regency complies with Permendagri No. 20 of 2018 and to investigate the Performance Allocation in the two villages. The study employs a descriptive qualitative method to collect relevant data. The financial management research conducted in Pineleng Satu Timur Village and Lotta Village indicates compliance with Permendagri Number 20 of 2018 for the planning, implementation, reporting, and accountability stages. However, non-compliance with Permendagri Number 20 of 2018 was found in the administration stage.